Large-scale paper supercapacitors on demand. (June 2022) - Brooke, Robert; Åhlin, Jessica; Hübscher, Kathrin; Hagel, Olle; Strandberg, Jan; Sawatdee, Anurak; Edberg, Jesper
Highlights: We present large scale energy storage using printed paper supercapacitors until 127.8 Farads in a single large device. A concept coined supercapacitors on demand was redesigned to allow individual, double and 4 devices in parallel and infinite devices in series (we present 4 in series). We show the large-scale paper supercapacitors can power an all-printed electrochromic artwork titled "Norrkoping Starry Night". Abstract: Clean, sustainable electrical energy could be the next greatest challenge and opportunity of mankind. While the creation of clean energy has been proven, the storage of such energy requires much more research and development. Battery and energy storage technology today relies heavily on rare metals which cannot support large production needs of society. Therefore, the need for energy storage technology to be created sustainably is of great importance. Recently, conductive polymers, a class of organic materials, have shown impressive results in energy storage but requires further development if this technology is to be implemented in various energy storage applications. Here, we report a new 'on demand' design for supercapacitors that allows for individual devices in addition to devices in parallel and in series to increase the capacitance and voltage, respectively. The individual device showed impressive capacity up to 10 F while increasing the area with the large parallel device increased the capacitance to a record 127.8 F (332.8 mF/cm 2 ). The 'on demand' design also allows paper supercapacitors to be in series to increase the operating voltage with an example device showing good charging behavior up to 5 V when 4 individual paper supercapacitors were arranged in series. Finally, the paper supercapacitors were incorporated into a prototype titled: 'Norrkoping Starry Night' which bridges the gap between art and science. An all-printed electrochromic display showing the city of Norrkoping, Sweden, complete with a touch sensor as an on/off switch and silicon solar cells to charge the paper supercapacitors is presented to bring several printed technologies together, highlighting the possibilities of the new paper supercapacitors within this report.